Digital Promotion Strategy Analysis in Developing Bukit Cinta Rawa Pening Tourist Destination: A Perspective of Managers and Business Actors - GULO, Sokhimano; PRANOTO, Pranoto (PT Keberlanjutan Strategis Indonesia, 2025)
The development of digital technology has encouraged the tourism sector to adapt its marketing strategies to increase destination attractiveness. This study aims to analyze the implementation of digital promotion strategies in the development of the Bukit Cinta Rawa Pening tourist destination from the perspectives of managers, business actors, communities, and tourists. The research method used is qualitative, with in-depth interview techniques applied to Semarang Regency Tourism Office staff, business people, local communities, and tourists. The results showed that digital promotion has had a positive impact on increasing tourists' awareness of the Bukit Cinta Banyu destination. Challenges faced include limited human resources and budget, a lack of understanding of digital marketing, and the minimal involvement of influencers and digital media in promoting this destination. In addition, information about the destination that is spread across various platforms is still not centralized and not always updated, making it difficult for tourists to access accurate information.